REFORM OF THE PRIVATE PENSION SYSTEM (SPP): PROPOSAL GUIDELINES - Romero Cerna, José Salvador (2015)
A comprehensive reform of the Pension System requi-res assessing the implementation of a universal pen-sion, the reform of the Private Pension System (SPP) and the reform of the Social Security Office (ONP). The article presents the general outlines of a proposal to reform the SPP that has as its central objective the welfare of workers and as a secondary objective, the development of the capital market. The main guideli-nes of the proposal are: the obligation to contribute to the SPP since age 25, differentiated contribution rates according to revenue cycle limits of worker savings, the admission of financial intermediaries providing pension savings products and/or investments, and the disposition of the accumulated fund at retirement, in specific cases.The proposal is suggested for the working class (trade unions, youth groups, etc.), so that it is contrasted with proposals of political organizations, whose leaders re-present the interests of economic groups and political organizations representing the interests of workers, so that if it is considered decent (adequate), they incor-porates some of the guidelines in the government plan in the upcoming presidential elections.